Adenosine deaminase (ADA) activity and isozymes in the serum of patients with hepatitis B compared with healthy people: a useful method in diagnosis clinical status - athari, seyyed shamsadin (Archives of Medical Laboratory Sciences, 2019)
Background: Adenosine deaminase (ADA) specifications (EC3.5.4.4) is an enzyme is involved in purine metabolism that breaks adenosine and deoxy-adenosine and produce inosine and deoxy-inosine and ammonia. The highest levels are of adenosine deaminase activity in monocytes and lymphocytes. High serum ADA activity with increased serum levels of AST, ALT and immunoglobulins were reported in variety of diseases including hepatitis. We aimed to investigate the activity of total ADA in serum of patients with hepatitis B and were determined molecular weight ADA1 and ADA2 isozymes in serum and RBC of hepatitis patients. Materials and Methods: We were defining experiments by electrophoresis on SDS-PAGE, for isozymes of ADA; ADA1 and ADA2 in serum and red blood cells. ADA1 molecular weight was estimated at about 35 KDa and ADA2 about 110 KDa. The total ADA activity was measured by the modified Ellis method in 37 patients with hepatitis B and 40 healthy controls in the age range (20-60 years). Results: The normal values for serum ADA in humans have been studied by various workers and found in serum samples to be in the range of 0-15 U/L, whiles in our analysis total ADA (tADA) enzyme activity is in controls and patients with hepatitis B, respectively, 13.35 ± 1.62 and 27.05 ± 8.49. Our results indicated that tADA level was higher in patients with hepatitis B than those of corresponding controls (P < 0.05).Total ADA enzyme activity shows a significant increase compared to the control group in all age groups tested. Conclusion: Therefore, the serum ADA level could be used as an index along with other parameters in follow up of patients with hepatitis B.